Maternal and Adult Interleukin-17A Exposure and Autism Spectrum Disorder - Fujitani, Masashi; Miyajima, Hisao; Otani, Yoshinori; Liu, Xinlang (Frontiers in Psychiatry, 2022)
Epidemiological evidence in humans has suggested that maternal infections and maternal autoimmune diseases are involved in the pathogenesis of autism spectrum disorder. Animal studies supporting human results have shown that maternal immune activation causes brain and behavioral alterations in offspring. Several underlying mechanisms, including interleukin -17A imbalance, have been identified. Apart from the pro-inflammatory effects of interleukin -17A, there is also evidence to support the idea that it activates neuronal function and defines cognitive behavior. In this review, we examined the signaling pathways in both immunological and neurological contexts that may contribute to the improvement of autism spectrum disorder symptoms associated with maternal blocking of interleukin -17A and adult exposure to interleukin -17A. We first describe the epidemiology of maternal immune activation then focus on molecular signaling of the interleukin -17 family regarding its physiological and pathological roles in the embryonic and adult brain. In the future, it may be possible to use interleukin -17 antibodies to prevent autism spectrum disorder.